2020
DOI: 10.1007/s10554-020-01969-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of myocardial work in arterial hypertension: insights from non-invasive left ventricular pressure-strain relations

Abstract: Background: A index of non-invasive myocardial work (MWI) can account for pressure during the assessment of cardiac function, potentially separating the influence of loading conditions from the influence of the underlying tissue remodelling. The aim is to assess LV function accounted for loading and explore hypertensive MWI distribution by comparing healthy individuals to hypertensive patients without and with localized basal septal hypertrophy (BSH).Methods and results: An echocardiogram was performed in 170 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 23 publications
4
35
0
1
Order By: Relevance
“…This was an unexpected finding since differences in BP were observed between our AN patients, OB patients and controls, confirming results of previous studies [7,8]. MW is a new variable that takes into account both deformation and afterload through interpretation of strain in relation to dynamic non-invasive LV pressure [12,13] (estimated using the method of Russel et al by measurement of cuff pressures [11,13,27]). The absence of differences in GMW between our groups, therefore, results from an interplay between the estimation of intraventricular pressure and the GLS curves, as shown by LV-PSL [11,13,30].…”
Section: Global Myocardial Work In Anorexia Nervosa (An) and Obesity (Ob) Patientssupporting
confidence: 90%
See 1 more Smart Citation
“…This was an unexpected finding since differences in BP were observed between our AN patients, OB patients and controls, confirming results of previous studies [7,8]. MW is a new variable that takes into account both deformation and afterload through interpretation of strain in relation to dynamic non-invasive LV pressure [12,13] (estimated using the method of Russel et al by measurement of cuff pressures [11,13,27]). The absence of differences in GMW between our groups, therefore, results from an interplay between the estimation of intraventricular pressure and the GLS curves, as shown by LV-PSL [11,13,30].…”
Section: Global Myocardial Work In Anorexia Nervosa (An) and Obesity (Ob) Patientssupporting
confidence: 90%
“…Recently, the non-invasive estimation of global myocardial work (GMW) by the assessment of LV pressure-strain loops (LV-PSL) has overcome this limitation by taking into account the loading conditions [11]. GMW, which reflects myocardial performance [12,13], cardiac glucose metabolism [14] and oxygen consumption [12], potentially enhances myocardial function assessment.…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with chronic pressure overload, when myocardial remodeling and hypertrophy appears, tissue fibrosis is more pronounced and correlates with the inability of the hypertrophied segments to increase their work during an acute pressure overload. MW indices will be lower in this subgroup of patients [21]. These results show that MW is more sensitive in detecting segmental tissue fibrosis even in the early stages and can add valuable information when measured alongside EF and GLS.…”
Section: Myocardial Work In Cardiac Diseasementioning
confidence: 58%
“…This was confirmed in a previously published study that included hypertensive patients. It was demonstrated that, in acute pressure overload, EF remains unaffected and GLS decreases while MW indices show an increase [21]. In these patients, work increases as every segment must provide more energy to pump against the raised afterload.…”
Section: Myocardial Work In Cardiac Diseasementioning
confidence: 99%
“…These data have been further confirmed by Tadic et al, who have also shown in hypertensive patients an additional impact on GCW of type-2 diabetes mellitus [ 28 ]. An analysis on 170 hypertensive patients also revealed an apex-to-base gradient in the distribution of MW, which reflected an impairment of the basal segments, compensated by the apical region, more pronounced in those with basal septal hypertrophy [ 59 ]. Thus, in the context of hypertensive patients MW seems to be more sensitive.…”
Section: Clinical Applicationsmentioning
confidence: 99%